2019
DOI: 10.14744/anatoljcardiol.2019.78178
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic treatment patterns and stroke prevention in patients with atrial fibrillation in TURKEY: inferences from GARFIELD-AF registry

Abstract: Objective: The corner stone of atrial fibrillation therapy includes the prevention of stroke with less adverse effects. The Global Anticoagulant Registry in the FIELD–Atrial Fibrillation (GARFIELD-AF) study provided data to compare treatment strategies in Turkey with other populations and every-day practice of stroke prevention management with complications. Methods: GARFIELD-AF is a large-scale registry that enrolled 52,014 patients in five sequential cohorts at >1.000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…In the recent GARFIELD-AF study conducted in Turkey, it has been reported that the frequency of NVAF is higher in women. 3 In addition, it was thought to be associated with obesity, metabolic syndrome, and cardiovascular diseases in Turkish women over 40 years of age. 3 Similarly, the female sex ratio was higher in NVAF patients in the previous AFTER study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the recent GARFIELD-AF study conducted in Turkey, it has been reported that the frequency of NVAF is higher in women. 3 In addition, it was thought to be associated with obesity, metabolic syndrome, and cardiovascular diseases in Turkish women over 40 years of age. 3 Similarly, the female sex ratio was higher in NVAF patients in the previous AFTER study.…”
Section: Discussionmentioning
confidence: 99%
“…CHA2DS2-VASc (heart failure, HT, age >75, diabetes, stroke, vascular disease, 65-74 age, and gender category female) risk score classification is widely used in our clinical practice to determine stroke risk. 3 Conventional treatment with vitamin K antagonists (VKA) in patients with non-valvular AF is replaced by non-vitamin K antagonist new oral anticoagulants (NOAC), either direct factor Xa inhibitors or direct thrombin inhibitors. 3 The Atrial Fibrillation: Epidemiological Registry (AFTER) study in Turkey, which is the first multicenter study conducted on AF patients in our country, showed that 40% of non-valvular AF (NVAF) patients were on warfarin treatment, but only 37% of this patients were in the effective international normalized ratio (INR) range; however, the most common reason for inadequate use of warfarin was physician negligence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary reasons for the lack of anticoagulant usage in patients with high stroke risk were physicians' concerns for bleeding events and patient refusal. 19 In our study, the four most important factors favoring non-OAC treatment were ESRD, history of myocardial infarct, history of major bleeding, and cancer. Second, among OAC patients, DOACs were used in 68.8%.…”
Section: Discussionmentioning
confidence: 59%
“…New oral anticoagulant (NOAC) therapy was replaced with antiplatelets when the bleeding risk was higher. Allcause mortality was higher in Turkey [13]. In addition RAMSES study showed that the awareness of stroke preventions strategies for NVAF has increased in Turkey and that more than two-thirds of NVAF patients were on OAC therapy.…”
Section: Discussionmentioning
confidence: 94%